The Effect of Environment Supports on Individual Creativity in Palestinian SMEs: Assessing the Mediating Role of General Self- Efficacy - Iriqat, Raed A. M. (International Review of Management and Marketing, 2019)
This paper aims to understand the mediating role of general self-efficacy in the effect of environment supports (work and none work environments) on individual creativity in Palestinian SMEs. Respondents for this paper are 247 of employees and owners in small and medium enterprises (SMEs) in North West Bank- Palestine. The findings show that work and non-work environments are significantly directly influenced on GSE, while, not directly influenced individual creativity. In addition, the results show that general self-efficacy plays a significant mediating role in enhancing the effect of environment supports on individual creativity in the Palestinian SMEs. Keywords: Environment Supports; Individual Creativity; General Self- Efficacy. JEL Classifications: M0, M10, M45 DOI: https://doi.org/10.32479/irmm.7397